Determinants of school attendance of young people in Argentina - Jorge A. Paz; Juan Carlos Cid (Universidad Autónoma de Baja California, 2012)
This paper analyzes the socioeconomic determinants of school attendance and time allocation of young people between 15 and 18 years old in Argentina. We are particularly interested in knowing the importance of each of them. The empirical analysis is based on a multinomial logit model for the period 1997-2009 with data coming from the Permanent Household Survey, Instituto Nacional de Estadística y Censos (INDEC), covering the urban population in the country.